Dynamic impedance compensation for WPT using a compensator in a three-coil wireless power transfer system. Issue 4 (5th November 2018) - Liu, Suqi; Tan, Jianping
Abstract : Purpose: The purpose of this paper is to study the wireless power transfer (WPT) system that always achieves the maximum output power at a fixed angular frequency using the dynamic impedance compensation and also the maximum transfer efficiency. Design/methodology/approach: An efficient topology of the WPT system is proposed which states that the functions of the relay are transformed into the functions of the compensator in the three-coil WPT system. Findings: Increasing the ratio of the frequency detuning factor of the compensator relative to the frequency detuning factor of the compensator also causes the curves of the normalized output power and the transfer efficiency to move toward the high frequency direction. Practical implications: The scheme of the dynamic compensation for the WPT using a compensator is convenient to obtain the dynamic impedance compensation by adding or removing the capacitances or inductances from the compensator. Originality/value: The functions of the relay are transformed into the functions of the compensator in the three-coil WPT system.